Análise comparativa de inversores multiníveis com células H-bridge conectadas em série - Zambra, Diorge Alex Báo (2006)
This Master Thesis presents a methodology to compare different topologies and configurations of multilevel systems applied to drive medium voltage induction motors. Initially, it presents the input and output parameters that must be supplied by the power drivesystems manufacturer. Then, the mathematical models of the performance indexes used are presented, being, the total harmonic distortion, first order distortion factor and the power losses of the main semiconductors devices. After, it is presented a methodology that allows the amplitude selection of DC sources for the inverter with a specific number of cascaded Hbridge cells. A study regarding the hybrid multilevel modulation strategies and the impact of their variations on the semiconductors devices power losses of the output inverter is developed. Based on this study, it is proposed a new hybrid multilevel modulation technique, it minimizes the semiconductors power losses and allow the use of front-end uncontrolled rectifiers without modifying the total harmonic distortion of the output voltage inverter. After, it is developed a comparative study between the asymmetrical hybrid multilevel inverter and the symmetrical multilevel inverter, which enables the determination of the switching frequency for the one determined performance and the maximum switching frequency of each converter. This Master Thesis presents complementary methods of design of the hybrid multilevel inverter and a methodology that will make possible to choose the drive system that presents high efficiency and reduced cost, neither penalizing the energy quality of the utility grid nor the induction motor constraints.